Predictive Model of Lung Function Disorders in Pesticide-Using Vegetable Farmers in Indonesia - Ajid, Andi; Habibi, Habibi; Ekasari, Ranti; Ansyar, Dian Ihwana; Wahyudiono, Yustinus Denny Ardyanto; Haqi, Dani Nasirul (Lambung Mangkurat University, 2025)
The use of pesticides by spraying can cause health problems such as pesticide poisoning, respiratory system problems which can affect lung capacity and can cause death if help is not given immediately. This study aims to determine the factors that influence lung capacity disorders in pesticide-using vegetable farmers in Kanreapia Village, Gowa Regency, Indonesia. The type of research used is quantitative with an analytical approach and uses a cross sectional study design. The population in this study was 216 farmers so that the sample size in this study was 83 farmers. The instruments used in this research were questionnaires and spirometry. The results of this study show that there is a relationship between spraying method p-value 0.003 and lung capacity, while age p-value 0.484, working duration p-value 0.117, working period p-value 0.959 and use of personal protective equipment p-value 0.367 have an insignificant relationship with lung capacity. Working period is the variable that has the greatest influence on lung capacity. It is recommended that farmer group leaders directly monitor work in the field regarding pesticide spraying carried out by farmer group members which could endanger them due to the risk of exposure to pesticides.